IMPLEMENTASI SISTEM ENTERPRISE RESOURCES PLANNING : STUDI FENOMENOLOGI DI PT PLATINUM CERAMICS INDUSTRY - Mastan, Stanislaus Adnanto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
Enterprise Resource Planning (ERP) is an information system for manufacture or service companies which has the role to integrate and to automate business processes that relate with operation aspects, production or distribution at the related companies. ERP system allows organizations to integrate variety of functions and business processes. This study aims to determine the impact and constraints to the implementation of ERP system in the Platinum Ceramics Industry (PCI) operations. ERP can provide real time information for managers and leaders, because of that on 2nd of August 2010 Platinum Ceramics Industry has done the information system change become ERP system. This study uses a phenomenological study approach. The result of this study are: (1) ERP system provide a positive impact for the company both in terms of operational, control and reporting; (2) ERP system minimizes manual processes and has the ability to be developed in accordance with the development of the company; (3) the constraints that exist make performance of the ERP system to be less than the maximum, the reliability of the information generated by the system become unreliable; and (4) ERP system for six months is still not able to contribute a report in accordance to the needs and expectations of management.Keywords: Enterprise Resource Planning, phenomenology study, operational activity.